Democratising Monograph Publishing or Preying on Researchers? Scholarly Recognition and Global 'Credibility Economies'. (3rd April 2022) - Mills, David; Robinson, Natasha
ABSTRACT: As the global university sector continues to expand, ever more academic work is being published, including growing numbers of academic monographs. Digital technologies open up opportunities for publishers to reach new academic communities. Drawing on interviews with authors and publishers, case-studies of two companies - Lambert Academic Publishing (Lambert) and Cambridge Scholars Publishing (CSP) - interrogate their inclusive, author-centred visions. Conceptualisations of academic 'credibility economies' strain to account for the different rationales academics have for publishing their work across a fragmented and multipolar global research system. Work has tended to focus on researchers' strategies for accumulating and managing credibility, rather than the structural blockages to, and the geographical constraints on, the flow of academic credibility. For researchers working at the margins of existing credibility economies, publishing an academic monograph is also about gaining global visibility and recognition. Promising to democratise publishing, the two publishers have both been accused of 'predatory' business practices. In response, CSP has sought to accumulate scholarly credibility, whilst Lambert rejects what it calls 'traditional' approaches to evaluating reputation and legitimacy. The two case-studies support a postcolonial critique of the 'predatory publishing' discourse, highlighting the exclusions and effacements enacted by the global academic publishing ecosystem.